Species composition of Bactrocera fruit flies (Diptera: Tephritidae) and their parasitoids on horticultural commodities in Batu City and Malang District, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Setiawan Y, Hamdoen FM, Muhammad FN, Hata K, Tarno H, Wang J. 2024. Species composition of Bactrocera fruit flies (Diptera: Tephritidae) and their parasitoids on horticultural commodities in Batu City and Malang District, East Java, Indonesia. Biodiversitas 25: 305-311. Bactrocera Macquart, 1835 fruit flies (Diptera: Tephritidae) are among the most important pests in horticultural commodities worldwide, including horticultural crops in Indonesia. Trapping is suggested to control, eradicate, and suppress fruit flies. The presence of natural enemies is a very important factor in the indicators of agroecosystem balance. This study aimed to monitor the species composition of Bactrocera fruit flies and their parasitoids in several horticultural commodities such as apples, large chili, red guava, sweet citrus, and tomatoes in Batu City and Malang District. Trapping and host-rearing methods were used in this research. A total of 7,124 individuals of Bactrocera were collected using a Steiner trap baited with methyl eugenol. They consisted of six species: Bactrocera carambolae Drew & Hancock, 1994; Bactrocera cucurbitae (Coquillett, 1899); Bactrocera dorsalis (Hendel, 1912); Bactrocera verbascifoliae Drew & Hancock, 1994; Bactrocera papayae Drew & Hancock, 1994; and Bactrocera umbrosa (Fabricius, 1805). The B. carambolae, B. dorsalis, and B. papayae were the three predominant species collected using Steiner traps baited with methyl eugenol. Based on the host-rearing method, B. carambolae and B. dorsalis were found in red guava fruit. Only one parasitoid species, Opius sp., was found in red guava fruit. These results provide valuable insights into the distribution of Bactrocera on horticultural commodities in Batu City and Malang District and the potential challenges regarding parasitoid presence.
Keywords: Bactrocera, diversity of fruit fly, fruit fly parasitoid, methyl eugenol, Steiner trap